Negotiating Parental designations among trans parents' families: An ecological model of Parental identity - Petit M.-P.; Julien D.; Chamberland L. (Psychology of Sexual Orientation and Gender Diversity, 2017)
Parental designations contribute to construct parental identity in the eyes of the child, the parent, and the generalized others. In a hetero/cisnormative context that offers only 2 options for parental identity (male fathers and female mothers), this study (a) provided an overview of the parental designations of trans people and their evolution as parents transitioned, (b) and generated a model of factors associated with the choice of posttransition parental designations. Semistructured interviews guided by the Bronfenbrenner’s ecological model (1988) were administered to 24 Canadian trans parents. The content of the interviews was analyzed using thematic analyses. Results showed that the choice of parental designations was influenced by the timing of childbirth, parents’ consideration of normative strains, negotiation with their children, and issues related to public spaces. Overall, trans parental identity appeared as a multidimensional, multidetermined, nonbinary, and fluid identity in a context of nonalignment between the sex assigned at birth and gender identity. Institutional forms and legislation relative to parenting and birthing must acknowledge the diversity of parental identity and designations.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; identités LGBTQIA2+; maternité; parentalité; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2264; sociologie; thématiques; transféminisme

Le ventre des femmes : capitalisme, racialisation, féminisme - Vergès, Françoise (Albin Michel, 2017)
Dans les années 1960-1970, l'État français encourage l'avortement et la contraception dans les départements d'outre-mer alors même qu'il les interdit et les criminalise en France métropolitaine. Comment expliquer de telles disparités? Partant du cas emblématique de La Réunion où, en juin 1970, des milliers d'avortements et de stérilisations sans consentement pratiqués par des médecins blancs sont rendus publics, Françoise Vergés retrace la politique de gestion du ventre des femmes, stigmatisées en raison de la couleur de leur peau. Dès 1945, invoquant la «surpopulation» de ses anciennes colonies, l'État français prône la régulation des naissances et l'organisation de l'émigration; une politique qui le conduit à reconfigurer à plusieurs reprises l'espace de la République, provoquant un repli progressif sur l'Hexagone au détriment des outre-mer, où les abus se multiplient. Françoise Vergés s'interroge sur les causes et les conséquences de ces reconfigurations et sur la marginalisation de la question raciale et coloniale par les mouvements féministes actifs en métropole, en particulier le MLF. En s'appuyant sur les notions de genre, de race, de classe dans une ère postcoloniale, l'autrice entend faire la lumière sur l'histoire mutilée de ces femmes, héritée d'un système esclavagiste, colonialiste et capitaliste encore largement ignoré aujourd'hui.
Keywords: 1900-1999; 1960-1969; 1970-1979; afrique; approches et analyses; corps; cours; discours dominant; europe; fem3100; france; féminisme décolonial; lit4700; maternité; premier cycle; périodes historiques; racisme; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; île de la réunion